Fuzzy Expert Advisory for E-Counselling - Taniza, Tajuddin (2004)

(untitled)
Fuzzy Expert is designed to mimic the human decision process of the modular system, maintains the value of based rules and using fuzzy logic control the describe uncertainty systems and utilizes the predominance of using expert systems to denote and control knowledge (Medeiros et. al., 1998). This paper presents the development of Fuzzy Expert Advisory for e-Counselling. The advisory model in counseling using a modular system for the psychology testing process for Behavioural Academic Self-Esteem (BASE) is used to test the prototype developed in this study. The system was constructed using a modular system for the psychology testing process for Behavioural Academic Self-Esteem (BASE)is used to test the prototype developed in this study. The system was constructed using hierarchical structural approach. The system was developed using web-based application language that is Microsoft's Active Server Pages (ASP) the server-side web scripting. The system comprises of five modules, namely Student Initiative of BASE Factor 1, Social Attention of BASE Factor 2, Success. Failure of BASE Factor 3, Social Attraction of BASE Factor 4, and Self-Confidence of BASE Factor 5. BASE test consists of sixteen items, categorized into the five main BASE factors. The Input to the system was first fuzzified and Fuzzy Associative Memory (FAM) table were constructed to handle the fuzzy rules of the five factors of BASE case study. The defuzzification known as Centre of Area (COA) is used to estimate the BASE factor and determine the level of academic self-esteem such as low self-esteem , moderate self-esteem, and high self-esteem. In addition, fuzzy expert advisory provides explanation and also explain how a diagnosis is reached for a particular case. The results showed that the fuzzy expert prototype system presented in this paper provided a reliable and accurate outcome after several test cases have been performed. Overall performance of this system was successfully tested and produced the results that were equal to an expert's judgment, thus accomplishing the set goals. The system has been verified by the counselors and the results produced by the system conform to the BASE factor rating scale and sub-scores.